2001
DOI: 10.1603/0022-2585-38.2.135
|View full text |Cite
|
Sign up to set email alerts
|

Aedes (Finlaya) japonicus(Diptera: Culicidae), a Newly Recognized Mosquito in the United States: Analyses of Genetic Variation in the United States and Putative Source Populations

Abstract: Introduction of potential disease vectors into a new geographic area poses health risks to local human, livestock, and wildlife populations. It is therefore important to gain understanding of the dynamics of these invasions, in particular its sources, modes of spread after the introduction, and vectorial potential. We studied the population genetics of Aedes (Finlaya) japonicus japonicus (Theobald), an Asian mosquito that was recognized for the first time in the United States in 1998. We examined patterns of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
96
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(100 citation statements)
references
References 39 publications
3
96
0
1
Order By: Relevance
“…Different populations of Ae. japonicus have been described in the eastern United States (18), and differences in vector competence between the populations may explain the discrepancy between the field and experimental data.…”
Section: Resultsmentioning
confidence: 92%
“…Different populations of Ae. japonicus have been described in the eastern United States (18), and differences in vector competence between the populations may explain the discrepancy between the field and experimental data.…”
Section: Resultsmentioning
confidence: 92%
“…saperoi are freshwater mountain forest stream breeders (Toma et al, 2001) and easily a ected by water quality of the breeding stream. With recent urbanization and deforestation, suitable breeding streams are at presently restricted to the northern part of Okinawajima and Iriomotejima.…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…ese subspecies show little morphological variation. Fonseca et al (2001) reported that Ae. j. japonicus was distinct from Ae.…”
mentioning
confidence: 99%
“…B 370: 20140136 with other vector species, Ae. j. japonicus is an outstanding model system because we have detailed data on the genetics of its expansion outside its native range [40][41][42][43][44]. This expansion is very recent but already extensive in continental USA, Europe and Hawaii, and occurred at a time when many mosquito surveillance programmes were already 'on alert' monitoring the expansion of Ae.…”
Section: Introductionmentioning
confidence: 99%